Case Study: Nursing Implementation of Fulfilling Self-Care Needs in Patients with Self-Care Deficits - Kamesyworo; An'umillah Fatharani, Nyimas (International Journal Scientific and Professional, 2023)
Self-care deficit is a person's inability to meet basic self-care needs independently. The purpose of the study was to achieve an overview of the implementation of adequate self-care needs in patients with self-care deficits. Descriptive research, with an implementation method using nursing care, with an assessment process, interviews, and direct observation carried out from 12 to 18 April 2021, The subjects of the case study were two schizophrenic patients with self-care deficit problems in the Bangau Room of Ernaldi Bahar Hospital, South Sumatra Province. The results of this study indicate that the provision of self-care needs is very effective in overcoming the problem of self-care deficits.